1983
DOI: 10.1002/1097-0142(19830901)52:5<868::aid-cncr2820520521>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc levels in normal and malignant tissues

Abstract: The copper and zinc levels in 53 malignant and 47 normal human tissue samples were measured. In the malignant tissues, the mean copper concentration was 46% higher (P < 0.001) than in the normal ones. Analysis of the individual organs showed this increment to be statistically significant in malignancies of the large bowel, stomach, urinary bladder and female reproductive organs, while in cancer of the breast, kidney and testis, the increase in copper level was not significant. The mean zinc concentration in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
170
1
3

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(179 citation statements)
references
References 20 publications
5
170
1
3
Order By: Relevance
“…Trace elements are essential micro-nutrients both for humans and other organisms. They are crucial for many physiological processes and are involved in many pathologic changes in tissues (1). On the other hand, it is well known that either an excess or a defi ciency of certain trace metals can lead to biological disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace elements are essential micro-nutrients both for humans and other organisms. They are crucial for many physiological processes and are involved in many pathologic changes in tissues (1). On the other hand, it is well known that either an excess or a defi ciency of certain trace metals can lead to biological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…They are crucial for many physiological processes and are involved in many pathologic changes in tissues (1). Thyroid hormones infl uence the metabolism of trace elements including copper (Cu) (2).…”
mentioning
confidence: 99%
“…Serum zinc levels are increased in melanoma patients (Ros-Bullon et al, 1998) but more often, reduced serum zinc levels are reported in breast (Sharma et al, 1994;Yucel et al, 1994), gallbladder (Gupta et al, 2005), lung (Diez et al, 1989;Issell et al, 1981), Hodgkin's disease (Cunzhi et al, 2001), colorectal (Gupta et al, 1993), neck (Buntzel et al, 2007), leukemia (Zuo et al, 2006) and thyroid (Al-Sayer et al, 2004) cancer patients. Elevated zinc levels in malignant tissues are observed in breast (Margalioth et al, 1983), intestinal (Kucharzewski et al, 2003), metastatic nasopharyngeal (Bay et al, 1997) cancers but are decreased in kidney carcinoma tissues (Margalioth et al, 1983). It is also high in bone marrow of patients with non-Hodgkin lymphomas (Schmitt et al, 1993).…”
Section: Association Of Zinc With Prostate Cancermentioning
confidence: 85%
“…The distribution of copper and its homeostasis plays a major role in many biological processes 41 and this is facilitated by the work of metal transporters and chaperones 42 , 43 & 44 . Disruption in pathways that transport copper can cause major damages in the form of metallostasis found in tumors 45 . The pathway is regulated by copper homeostasis genes and recent transcriptome analysis of copper homeostasis genes have shown the upregulation of SLC31A1, SCO and COX11 in colorectal cancer cases 46 .…”
Section: Sco1-wnt10b-x Combinationsmentioning
confidence: 99%